Electrochemical characterization of mesoporous nanographite films. (August 2016) - Magdesieva, Tatiana V.; Shvets, Petr V.; Nikitin, Oleg M.; Obraztsova, Ekaterina A.; Tuyakova, Feruza T.; Sergeyev, Vladimir G.; Khokhlov, Alexey R.; Obraztsov, Alexander N.
Abstract: The mesoporous nanographite (NG) film material consisting of tiny flake-like graphite crystallites of nanometer-scale thickness is deposited onto carbon fibers with diameter of few micrometers using adapted plasma enhanced chemical vapor deposition (CVD) method. Macroscopic morphology parameters of NG material depend on deposition time duration so, that thickness of the NG coating is increased from 0.5 to 2 μm, whereas the average sizes of the individual crystallites and the pores between them are decreased from 0.5 to 0.1 nm, with deposition time extension from 15 to 60 min, respectively. The high resolution electron microscopy examinations indicate that the NG flakes consist of parallel graphene layers separated by about 0.34 nm and those layers are paired at the edges of the flakes producing arced structures. The electrochemical capacitance measurements were served for characterization of the mesoporous nanographite coating; the specific capacitance arising from the electrostatic charge accumulated at the electrode–electrolyte interface was estimated using cyclic voltammetry, galvanostatic charge/discharge measurements, and electrical impedance spectroscopy. The effects of the deposition time duration and other parameters of CVD process on electrochemical performance and structural properties of the prepared NG films are to be discussed.